﻿Phytochemical screening, antibacterial, antioxidant, and anticancer activity of Coffee parasite acetone extract (Loranthus ferrugineus Roxb) - Tita Juwitaningsih; Destria Roza; Saronom Silaban; Elvira Hermawati; Neneng Windayani (Pensoft Publishers, 2022)
This study aimed to perform a phytochemical screening and test the antibacterial, antioxidant, and anticancer activities of acetone extracts of the Coffee parasite (Loranthus ferrugineus Roxb). A phytochemical screen was performed using specific reagents. Antimicrobial testing was performed using the paper disc diffusion method. The antioxidant activity test used the 2,2-diphenyl-1-picrylhydrazyl (DPPH) method. Anticancer activity test against HeLa and A549 cells based on the 3-(4,5-Dimethylthiazol-2-yl)-2,5-Diphenyltetrazolium Bromide (MTT) assay method. Acetone extract L. ferrugineus Roxb contains alkaloids, flavonoids, triterpenoids, and tannins compounds. The acetone extract of L. ferrugineus Roxb showed activity against all the bacteria tested, with the inhibition zone diameter ranging from 6.2 mm - 11.1 mm. Acetone extract of L. Ferrugineus Roxb had a very strong antioxidant activity with a value of IC50 = 48.7122 µg/mL. The anticancer activity test showed cytotoxic activity against HeLa cells with a value of IC50 = 47.62 µg/mL and for A549 cells with a value of IC50 = 192.83 µg/mL.